Consequence models for vented hydrogen deflagrations: CFD vs. engineering models. (2nd April 2019) - Lakshmipathy, S.; Skjold, T.; Hisken, H.; Atanga, G.
Abstract: This paper compares two approaches for predicting the consequences of vented hydrogen deflagrations: empirical engineering models (EMs) and computational fluid dynamics (CFD) simulations. The study is part of the project 'Improving hydrogen safety for energy applications through pre-normative research on vented deflagrations' (HySEA), funded by the Fuel Cells and Hydrogen 2 Joint Undertaking (FCH JU) under grant agreement No 671461. The HySEA project focuses on vented hydrogen deflagrations in containers and smaller enclosures with internal congestion representative of industrial applications. Data from experiments conducted as part of the HySEA project are used to evaluate predictions from a selection of EMs and the CFD tool FLACS. The experiments involve various obstacle and venting configurations, and initially quiescent homogeneous hydrogen-air mixtures with hydrogen concentrations in the range 15–24 vol%. There is a significant scatter in the maximum reduced overpressures predicted by the different EMs in the present study. For certain configurations, there is an order of magnitude difference between the different EM predictions. Two versions of the CFD tool FLACS are used in the present study: i) the standard commercial release FLACS v10.7r2, and ii) an in-house development version termed FLACS-beta. The commercial release generally over-predicts the maximum overpressures measured in the experiments, while the development version of FLACS gives improved results for several configurations. Highlights: Compared various engineering model predictions against CFD model calculations for vented deflagrations. Evaluated two different versions of FLACS performance for vented hydrogen deflagrations. Evaluated Engineering model predictions for vented Hydrogen deflagrations. Discussed effects of congestion variation, confinement variation, and fuel concentration on vented deflagrations.